knowledge of dentists in RSGM Faculty of Dentistry, Trisakti University regarding the prevention and infection management of Covid-19 in dental practice - Liusa Harry Dinata (Yayasan Pendidikan Medika Indonesia, 2022)
Background: With the increasing number of Covid-19 cases, as well as new variants and discoveries in Indonesia, many health issues start to arise in the society, one of which is in the practice of dentistry. Dentists have a very high risk of being infected from Covid-19 virus, therefore it is important for them to have a comprehensive understanding regarding Covid-19 prevention and infection management, especially in dental practice. Objective: to measure the knowledge of dentists in RSGM Faculty of Dentistry, Trisakti University regarding the prevention and infection management of Covid-19 in dental practice. Methods: Knowledge measurement is done by utilizing online questionnaire through google forms which consists of 16 multiple choice questions with 4 choices. The questionnaire includes questions related to the prevention and infection management of Covid-19. The knowledge of respondents will be classified into 3 categories, namely high, medium, and low. Respondents will be categorized to have a high level of knowledge if they manage to answer 12-16 questions correctly. Respondents will be categorized to have a medium level of knowledge if they are able to answer 9-11 questions correctly. Meanwhile, respondents who answered correctly no more than 9 questions will be classified into the category of low knowledge level. Results: From a total of 56 respondents, 53.6% of them have high level of knowledge, 42.1% have medium level of knowledge, and the rest 5.3% have low level of knowledge regarding the prevention and infection management of Covid-19 in dental practice. Conclusion: The result of this study shows most of the dentists in RSGM Faculty of Dentistry, Trisakti University have an above average level of knowledge regarding Covid-19 prevention and infection management in dental practice.